New Faculty's Perception of Faculty Development Initiatives at Small Teaching Institutions. (16th August 2012) - Puri, Aditi; Graves, Daren; Lowenstein, Arlene; Hsu, Lily
Abstract : New faculty at small teaching institutions experience varied challenges related to navigation of three academic pillars: teaching, scholarship, and service. New faculty are often not prepared by doctoral or terminal degree granting institutions for faculty roles. This increases the responsibility of the hiring institution to introduce new faculty to the academic culture and provide development opportunities aimed at promoting academic success. For the purpose of this study seventeen faculty members, employed between one and three years at four northeastern USA colleges, were recruited for interviews. The Motivation-Hygiene Theory was applied to study the impact of challenges, barriers, and facilitators on faculty satisfaction with faculty development initiatives. The qualitative results emphasize a need for institutions to enhance the new faculty development initiatives: comprehensive new faculty orientations, ongoing teaching and learning workshops, mentoring programs, and other methods to facilitate the transition of faculty to the new academic position.